Development of Local Wisdom-Based LKPD on the Marine Resources of Raja Ampat for Grade IV Elementary School Presidential Instruction No. 08 Kampung Urbinasopen - Jumadi, Nurhaliza; Apia, Gika; Hafid, Abdul (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
This study aims to develop Student Worksheets (LKPD) based on local wisdom of marine resources in Raja Ampat using the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). The study was conducted to examine the validity, practicality, and initial effectiveness of LKPD in teaching science to Grade IV students at SD Inpres No. 08 Kampung Urbinasopen. The participants included 15 students, one classroom teacher, and five expert validators. The school has a total of 118 students (55 males, 63 females), guided by 7 professional teachers. Data were collected using questionnaires, observations, learning outcome tests, and interviews. The results showed that the LKPD obtained a validity score of 91.2% (very valid), practicality 93.4% (very practical), and an improvement in learning outcomes from 52.3 (pretest) to 73.4 (posttest). The local wisdom-based LKPD provides authentic learning experiences, increases student engagement, and supports the understanding of science concepts.